Feto-maternal outcome study in hypertensive disorders of pregnancy: primigravida vs multigravida - Mandal, Jaydeb; Roy, Dibyendu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Approximately 7-10% of all pregnancies are complicated by some form of hypertensive disorders. Hypertensive disorders of pregnancy (HDP) are major cause of maternal morbidity and mortality as well as fetal complications. This study is aimed to determine and compare the maternal and perinatal outcomes of hypertensive pregnancies in between primigravida and multigravida. Methods: After taking college ethical committee permission a prospective comparative study was done in our medical college from January 2017 to April 2017 with 300 women having HDP from 3658 admitted patients in that time. They were enquired and followed up as per questionnaire till their discharge from the hospital. Among study women 174 women were primigravida, 126 were multigravida. The prevalence of maternal events and complications like eclampsia, IUGR, preterm labour (PTL), HELLP syndrome DIC, mode of delivery and fetal events like Apgar’s score, birth weight were studied and compared among primigravida and multigravida. All the events related to pregnancy outcomes were analyzed statistically. Results: Our study shows prevalence of HDP was 8.2% of total admitted patients, of them 58% were primigravida, 42% multigravida. Primigravida compared to multigravida had a higher tendency to have IUGR, PTL. DIC is also slightly more in primigravida but placental abruption and PPH were more in multigravida. Fetal outcome study showed babies born with low birth weight is significantly more in primigravida and higher incidence of severe asphyxiated babies were born in primigravida. More than 40% primigravida were terminated by caesarean section, most of them had emergency indication. Conclusions: Primigravidas are more sufferer to HDP and its complications. Comprehensive antenatal care at the same time strict vigilance during delivery and quality postnatal care of high risk patients specially primigravida group could significantly reduce maternal morbidity and mortality and improves fetal outcome.